Weaving the Text in Ovid, Metamorphoses, 6. 424-674 (Circe de clásicos y modernos, 2018)
The tale of Procne, Philomela and Tereus in Ovid’s Metamorphoses (6.424-674) presents one of the most violent Greco-Roman mythic stories. Philomela’s sexual attack and glossectomy, and Itys’s filicide with the later cannibal banquet function as the main instances of the Ovidian narration. Considering different theoretical approaches to the legend, I will explore specifically the construction of the narrative process that culminates in the three final metamorphoses. My reading aims to identify some diegetic and stylistic features of a poetics based on inversion and paradox. I will highlight some self-reflexive markers whereby the answer to “quid faciat Philomela?” (572) exhibits actually quid facit poeta.
Keywords: Ovid; Metamorphoses; narrative process; inversion; paradox